Increased expression of transferrin receptor 1 in the brain cortex of 5xFAD mouse model of Alzheimer’s disease is associated with activation of HIF-1 signaling pathway - Petralla, Sabrina; Saveleva, Liudmila; Kanninen, Katja M.; Oster, Julia S.; Panayotova, Maria; Fricker, Gert; Puris, Elena (Molecular neurobiology, 2024)
Alzheimer’s disease (AD) is the most common cause of dementia. Despite intensive research efforts, there are currently no effective treatments to cure and prevent AD. There is growing evidence that dysregulation of iron homeostasis may contribute to the pathogenesis of AD. Given the important role of the transferrin receptor 1 (TfR1) in regulating iron distribution in the brain, as well as in the drug delivery, we investigated its expression in the brain cortex and isolated brain microvessels from female 8-month-old 5xFAD mice mimicking advanced stage of AD. Moreover, we explored the association between the TfR1 expression and the activation of the HIF-1 signaling pathway, as well as oxidative stress and inflammation in 5xFAD mice. Finally, we studied the impact of Aβ1-40 and Aβ1-42 on TfR1 expression in the brain endothelial cell line hCMEC/D3. In the present study, we revealed that an increase in TfR1 protein levels observed in the brain cortex of 5xFAD mice was associated with activation of the HIF-1 signaling pathway as well as accompanied by oxidative stress and inflammation. Interestingly, incubation of Aβ peptides in hCMEC/D3 cells did not affect the expression of TfR1, which supported our findings of unaltered TfR1 expression in the isolated brain microvessels in 5xFAD mice. In conclusion, the study provides important information about the expression of TfR1 in the 5xFAD mouse model and the potential role of HIF-1 signaling pathway in the regulation of TfR1 in AD, which could represent a promising strategy for the development of therapies for AD.
Gesehen am 16.08.2024